Development delay in children with severe acute malnutrition and its association with Vitamin B12 deficiency - Adhualia, Aishvarya; Maurya, Manisha; Tewari, A. D. (International Journal of Contemporary Pediatrics, 2019)
Background: About half of the under five children are malnourished in India and so is morbidity associated with it. Malnutrition is also associated with multiple vitamin deficiency one of which is vitamin B12. Vitamin B12 is essential for DNA, RNA and protein synthesis; and for myelination of brain during the early childhood period. Deficiency of vitamin B12 can lead to megaloblastic anemia and neurological problems. So, authors aimed to look prevalence of vitamin B12 deficiency and; its hematological and neurological effects in severe acute malnourished children. Methods: it was an observational case control study, in which severe acute malnourished (SAM) children aged 0- 59 months who were admitted in Nutritional Rehabilitation Centre (NRC) were enrolled. Vitamin B12 levels were estimated and levels <200 pg/ml, 200-350 pg/ml, and >350 pg/ml were considered deficient, insufficiency and sufficient. Complete blood count was done for hematological effects and; developmental assessment was done to look for neurological effects. Results: Vitamin B12 was deficient, insufficient, normal in 15(16.3%), 25 (27.5%) and 52 (56.5%) children respectively. Vitamin B12 deficiency was significantly associated with hyperpigmentation and glossitis. Infant and young child feeding practices were not associated vitamin B12 deficiency. Macrocytic anemia was found in 23.4% SAM children and macrocytosis was not significantly associated with vitamin B12 deficiency. Developmental delay was found in 55.3 % children and was not significantly associated with severe acute malnutrition. Conclusions: There is high prevalence of Vitamin B12 deficiency and insufficiency in children with severe acute malnourished children. Macrocytic anemia and developmental delay are not significantly associated with vitamin B12 deficiency.